2018
DOI: 10.1155/2018/8516498
|View full text |Cite
|
Sign up to set email alerts
|

Coprecipitation Method of Synthesis, Characterization, and Cytotoxicity of Pr3+:LaF3 (CPr = 3, 7, 12, 20, 30%) Nanoparticles

Abstract: The Pr3+:LaF3 (CPr = 3, 7, 12, 20, 30%) nanoparticles were characterized by means of high-resolution transmission electron microscopy, X-ray diffraction, optical spectroscopy, energy dispersive X-ray spectroscopy, dynamic light scattering, and MTT assay. It was revealed that the average diameter of all the NPs is around 14–18 nm. The hydrodynamic radius of the Pr3+:LaF3 (CPr = 7%) nanoparticles strongly depends on the medium. It was revealed that hydrodynamic radii of the Pr3+:LaF3 (CPr = 7%) nanoparticles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The reduction of Pr 3+ :LaF 3 lattice parameters apparently related to crystal lattice distortion. The radius of Pr 3+ (0.105 nm) is smaller than that of La 3+ (0.113 nm) due to the lanthanide contraction, so the cell volume of Pr 3+ :LaF 3 reduces with more Pr 3+ replacing La 3+ [14].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The reduction of Pr 3+ :LaF 3 lattice parameters apparently related to crystal lattice distortion. The radius of Pr 3+ (0.105 nm) is smaller than that of La 3+ (0.113 nm) due to the lanthanide contraction, so the cell volume of Pr 3+ :LaF 3 reduces with more Pr 3+ replacing La 3+ [14].…”
Section: Resultsmentioning
confidence: 98%
“…Among these methods of synthesis, a coprecipitation method is considered one of the cheapest and easiest methods of synthesis of NPs [13]. On the one hand, it provides a synthesis of LnF 3 NPs with desired size, shape, and structure [14]. Usually, this method does not require toxic organic precursors as well as sophisticated and expensive laboratory equipment.…”
Section: Introductionmentioning
confidence: 99%
“…e single core NPs were synthesized via the coprecipitation method [35]. In order to synthesize both Pr 3+ : LaF 3 (C Pr � 1%) nanospheres and nanoplates, 0.04 g of Pr 2 O 3 and 4.00 g of La 2 O 3 were added to 85 mL of 10% nitric acid in a glass beaker.…”
Section: Synthesis Of the Nanoparticlesmentioning
confidence: 99%
“…For both core and core/shell nanoplates, the interlayer distance between two fringes which are parallel to the upper and lower pedestals of the plate was measured to be ∼0. 35 nm which corresponds to the [002] plane of the LaF 3 crystal. Hence, it can be suggested that the preferred growth of the nanoplates takes place along both [100] and [010] planes under the existing conditions of synthesis [42].…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation